Administration of Ultra Disperse Nanoparticles to Create Hyperthermia In vitro and In vivo, for the Treatment of Cancer Diseases by Brownian and Neel Mechanisms - Zviad Kovziridze; Jurgen G. Heinrich; Reinhard Goerke; Gregor Mamniashvili; Zurab Chachkhiani; Nunu Mitskevich; Giorgi Donadze (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Background: Magnetic hyperthermia is a technique that proposes the annihilation of cancer cells through the elevation of cell temperature above 316K by utilizing the heat dissipated by magnetic particles exposed to an alternating magnetic field. Aim: The idea of the invention is that Ultradisperse superparamagnetic nanoceramic particles are received in rotating cathode equipment. Methods: The microstructure of powder is studied by electronic microscopy and X-ray analysis. Also, powder homogeneity, particle size distribution and, respectively, stability and magnetic susceptibility are studied by magnetometric method. The average sizes of particles are 30-100 nm. The powder is homogeneous and in the process of analysis, it was revealed its good stability. The research object is superparamagnetic powder. The relative value of its magnetic susceptibility is 1.00037. Sample magnetization measurements are done at cooling in zero magnetic field (ZFC) and in nonzero field (FC) modes, also magnetic hysteresis curves are measured at low and high temperatures compared to the mean blocking temperature (TB) for measured samples. From the state of maximum on the ZFC curve, it was deduced that the temperature of blocking in the given superparamagnetic subsystem of particles is TB 60 K. Results: The practical innovation is that for the first time in Georgia, the local monotherapy and adjuvant effects of locally controlled hyperthermia in the polychemotherapeutic treatment of tumors were studied with the help of the created devices. For the first time in Georgia, medical devices for locally controlled hyperthermia were developed. Accordingly, with the help of these devices, an innovative technology for hyperthermia was created. Conclusion: A completely new methodology and technology is being created. Significant progress has been made in experiments on animals and voluntary patients.